Clinical Efficacy of Infantile Massage in the Treatment of Infant Functional Constipation: A Meta-Analysis - Liu, Zhi; Gang, Li; Yunwei, Ma; Lin, Ling (Frontiers in Public Health, 2021)
Background: Functional constipation in children is an important disease that causes a psychological burden on infants and young children across the world. It will greatly affect children’s quality of life in early childhood, and even affect their psychological and physical health. At present, children’s functional constipation is treated with drugs alone, but it will produce drug dependency. In recent years, Traditional Chinese Medicine (TCM) infant massage has been used as a complementary and alternative therapy, and its effectiveness and safety has been confirmed, which has aroused the attention of pediatricians of internal medicine and surgery. Objective: This study aimed to determine the effectiveness and safety of infant massage in the treatment of children's functional constipation through 13 randomized controlled trials (RCTs). Methods: The randomized controlled trials (RCTs) on TCM infant massage in the treatment of children's functional constipation were searched from 11 databases (PubMed, Springer, ElsevierScience, Cochrane Library, Scopus, Ovid (Medline, EMBASE, PsycInfo), Orbis, WebofScience, CNKI, WANFANG, VIP). Inclusion criteria: Eligible RCTs were included to compare the effects of infant massage intervention on defecation frequency and consistency. Data extraction: Two evaluators extracted the data. Count data were expressed as relative risk (RR), measurement data were expressed as weighted mean difference (WMD). The interval estimation adopted 95% confidence interval (95% CI). Results: The clinical evidences of 13 RCTs showed that, compared to drug therapy alone, TCM infant massage had a superior effect on the treatment of children's functional constipation, and its effectiveness was 4.81 (95% CI 3.60, 6.43) by the meta-analysis. In terms of lowering the scores of stool form -0.30 (95% CI -0.38, -0.22), difficult defecation -0.73 (95% CI-0.81, -0.65), and constipation symptoms -0.26 (95% CI-0.28, -0.25), etc., TCM infant massage was superior to drug therapy. Due to the small sample size of some RCTs included, the reliability and validity of the conclusions may be affected; Conclusion: This study shows that TCM infant massage can increase the defecation frequency and reduce the symptoms of constipation in children; in addition, the clinical trial has good safety, with few adverse events, and it has a very beneficial effect.